2018
DOI: 10.1111/jocn.14177
|View full text |Cite
|
Sign up to set email alerts
|

The art of oral handovers: A participant observational study by undergraduate students in a hospital setting

Abstract: Aims and objectives: To explore the conditions for oral handovers between shifts in a hospital setting, and how these impact patient safety and quality of care.Background: Oral handovers transfer patient information and nursing responsibilities between shifts. Short written summaries of patients can complement an oral handover. How to find the balance between a standardised protocol for handovers and tailoring variations to specific patients and situations is debated in the literature.Oral handovers provide ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
1
13
0
4
Order By: Relevance
“…The interviews were semi‐structured with predefined themes regarding information practice. The interview guide was developed based on results of previous studies; for example, we found several studies on the use of different handover styles and thus found it important to explore how the nurses received information at the beginning of their shift (Giske et al, ; Meissner et al, ). Questions regarding the piloting of standardised care plans were based on the Unified Theory of Acceptance and Use of Technology (Venkatesh, Thong, & Xu, ) (see Table for main themes of the interview guide).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interviews were semi‐structured with predefined themes regarding information practice. The interview guide was developed based on results of previous studies; for example, we found several studies on the use of different handover styles and thus found it important to explore how the nurses received information at the beginning of their shift (Giske et al, ; Meissner et al, ). Questions regarding the piloting of standardised care plans were based on the Unified Theory of Acceptance and Use of Technology (Venkatesh, Thong, & Xu, ) (see Table for main themes of the interview guide).…”
Section: Methodsmentioning
confidence: 99%
“…The interviews were semi-structured with predefined themes regarding information practice. The interview guide was developed based on results of previous studies; for example, we found several studies on the use of different handover styles and thus found it important to explore how the nurses received information at the beginning of their shift (Giske et al, 2018;Meissner et al, 2007).…”
Section: Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…O comportamento do profissional durante a transferência implica na qualidade da comunicação interprofissional. A realização de multitarefas ou de tarefas não urgentes, contribuíram para distrações e interrupções durante a transferência 26,27 . As interrupções são vistas pelos profissionais como uma falta de respeito, assim como a dificuldade para transferir a responsabilidade do paciente entre os profissionais foi um fator que contribuiu para a falha da comunicação 26 .…”
Section: Discussionunclassified
“…Earlier research has shown that the quality of nursing care can be affected by the way patients are presented, for example in nurses' verbal reports. 41 Students in this study report striving to form their own unprejudiced opinions and thus trying to disregard possible stereotypical characteristics of patients 42 being transferred from their preceptors. Thus, students try to avoid the continuing of reproduction of inequality based on social stereotypes.…”
Section: Discussionmentioning
confidence: 99%